PERSPEKTIF ETIKA TERAPAN KRISTEN TERHADAP KASUS ABORSI - Febrian, Cindy Clarissa Gabriela; Herman, Samuel; Simanjuntak, Ferry (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2025)
Abortion is a controversial and complex issue, encompassing a wide range of conflicting perspectives. In the context of Christianity, views on abortion are generally closely related to theological understandings of the intrinsic value of human life, the dignity of being created in the image of God, and the moral responsibility to protect life. This article presents a theological and Christian ethical review of abortion by examining biblical approaches, Church teachings, and various arguments both supporting and opposing the practice of abortion from a Christian point of view. In addition, this article explores the impact of abortion on individuals, society, and church communities, and evaluates the Church's perspective and pastoral role in providing guidance, understanding, and support to individuals involved in the complex decision-making process surrounding abortion.